2014
DOI: 10.1371/journal.pone.0110651
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Batterers in Treatment: Empirical Support for a Distinction between Type I, Type II and Type III

Abstract: This study explores the existence of different types of batterers in a sample of 266 men who had been court referred for intimate partner violence. The data collected in the assessment that have been used to perform a hierarchical and a two-step cluster analysis fall into three areas: aggression towards the partner, general aggression and presence of psychopathology and personality traits, more specifically, alcohol use, borderline and antisocial personality traits, psychopathy traits, state anger and trait an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(60 citation statements)
references
References 38 publications
9
51
0
Order By: Relevance
“…In all the other variables, this group was located between groups GVA and FO. As in previous studies in European and Latin American settings, the results of the present study replicate the different types of batterers in Holtzworth-Munroe and Stuart's (1994) typology in a Spanish sample of court-referred IPV batterers, thus confirming its cross-cultural validity (Cunha & Gonç alves, 2013;Graña et al, 2014;Johnson et al, 2006;Thijssen & de Ruiter, 2011).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In all the other variables, this group was located between groups GVA and FO. As in previous studies in European and Latin American settings, the results of the present study replicate the different types of batterers in Holtzworth-Munroe and Stuart's (1994) typology in a Spanish sample of court-referred IPV batterers, thus confirming its cross-cultural validity (Cunha & Gonç alves, 2013;Graña et al, 2014;Johnson et al, 2006;Thijssen & de Ruiter, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…In the Spanish setting, the study of typologies has mainly focused on limited samples of IPV batterers in prison or a combination of court-referred and prison batterers (Loinaz, 2014;Llor-Esteban, García-Jiménez, Ruiz-Hernández & Godoy-Fernández, 2016;Ruiz-Hernández, García-Jiménez, Llor-Esteban, & Godoy-Fernández, 2015). In the court-referred context only, Graña, Redondo, Muñoz Rivas, and Cantos (2014) classified a large sample of IPV batterers into three types according to risk level (low, moderate, and high), similar to the typology proposed by Cavanaugh and Gelles (2005).…”
mentioning
confidence: 99%
“…The authors identified three types of perpetrators common in all typology research and these were low, moderate and high risk offenders Cavanaugh & Gelles, 2005). This refined typology is supported through recent research (Graña, Redondo, Muñoz-Rivas, & Cantos, 2014). This typology may be useful, but supports the concern that there is a lack of evidence about the distinction of different types and consequently utility of these types.…”
Section: Discussionmentioning
confidence: 67%
“…It is evident that most of these interventions have gone to great efforts to enrich their programs by including elements of other approaches (e.g., CBT, client-centered), and a few of them have incorporated in their protocols the screening for different types of perpetrators. Recent empirical research with batterers (Graña, Redondo, Muñoz-Rivas, & Cantos, 2014) describes the benefits of tailoring interventions to specific types of perpetrators. Among these benefits are the reductions of recidivism, program dropout rates, and increased ability to predict program success.…”
Section: Views On Standards To Regulate Interventions For Perpetratormentioning
confidence: 99%
“…This trend is also reflected in the scarce number of academics involved in conducting data collection/program assessment. Therefore, a proposed standard of practitioners liaising with academics is essential to link research to practice, particularly cutting-edge evidence-based research to identify and devise more effective interventions in terms of achieving lower recidivism and program dropout rates (Dixon, Archer, & Graham-Kevan, 2012;Graña et al, 2014;Hershenberg, Drabick, & Vivian, 2012).…”
Section: Views On Standards To Regulate Interventions For Perpetratormentioning
confidence: 99%